Liquid chromatography with tandem mass spectrometry method for the simultaneous determination of multiple sweet mogrosides in the fruits of Siraitia grosvenorii and its marketed sweeteners. Issue 21 (5th October 2016) - Luo, Zuliang; Shi, Hongwu; Zhang, Kailun; Qin, Xijun; Guo, Yuhua; Ma, Xiaojun
Abstract : A high‐performance liquid chromatography with electrospray ionization tandem mass spectrometry method has been developed and validated for the simultaneous quantification of eight major sweet mogrosides in different batches of the fruits of Siraitia grosvenorii and its marketed sweeteners. The sample preparation procedure and chromatographic and mass spectrographic conditions were optimized. Chromatographic separation was achieved on a reversed‐phase Poroshell 120 SB C18 column in 10.0 min with gradient elution with acetonitrile and water, both of which contained 0.1% formic acid. The multiple reaction monitoring scanning mode was employed for quantification in the negative ion mode. The developed method was validated with acceptable linearity ( r 2 = 0.9984–0.9998) over a wide concentration range, precision (relative standard deviations = 1.09–3.91%), stability (relative standard deviations = 1.21–3.01%), and recovery in the range of 91.22–106.58% (relative standard deviations ≤ 3.79%) under optimum conditions. The proposed method was demonstrated to be simple, rapid, specific, and reliable and was successfully applied for the quality control of the fruits of S. grosvenorii and its marketed sweeteners.